Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's solve each part step by step.
### Part (a)
[tex]\[ \log_8 3 + \log_8 7 = \log_8 (\boxed{\phantom{}}) \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b(a) + \log_b(c) = \log_b(a \cdot c) \][/tex]
we combine the two logarithms:
[tex]\[ \log_8 3 + \log_8 7 = \log_8 (3 \cdot 7) \][/tex]
[tex]\[ \log_8 3 + \log_8 7 = \log_8 21 \][/tex]
So, the missing value is:
[tex]\[ \boxed{21} \][/tex]
### Part (b)
[tex]\[ \log_4 5 - \log_4 \boxed{\phantom{}} = \log_4 \frac{5}{7} \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b(a) - \log_b(c) = \log_b \left(\frac{a}{c}\right) \][/tex]
we can set up the equation:
[tex]\[ \log_4 5 - \log_4 7 = \log_4 \left(\frac{5}{7}\right) \][/tex]
So, the missing value is:
[tex]\[ \boxed{7} \][/tex]
### Part (c)
[tex]\[ \log_5 \frac{1}{9} = -2 \log_5 \boxed{\phantom{}} \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b \left(a^c\right) = c \log_b(a) \][/tex]
we rewrite the equation:
[tex]\[ \log_5 \frac{1}{9} = -2 \log_5 3 \][/tex]
Recognize that:
[tex]\[ 3^2 = 9 \][/tex]
and
[tex]\[ \frac{1}{9} = 3^{-2} \][/tex]
Thus,
[tex]\[ \log_5 \frac{1}{9} = \log_5 (3^{-2}) \][/tex]
which simplifies by the logarithmic power rule:
[tex]\[ \log_5 (3^{-2}) = -2 \log_5 3 \][/tex]
So, the missing value is:
[tex]\[ \boxed{3} \][/tex]
To summarize, the missing values are:
(a) [tex]\(\boxed{21}\)[/tex]
(b) [tex]\(\boxed{7}\)[/tex]
(c) [tex]\(\boxed{3}\)[/tex]
### Part (a)
[tex]\[ \log_8 3 + \log_8 7 = \log_8 (\boxed{\phantom{}}) \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b(a) + \log_b(c) = \log_b(a \cdot c) \][/tex]
we combine the two logarithms:
[tex]\[ \log_8 3 + \log_8 7 = \log_8 (3 \cdot 7) \][/tex]
[tex]\[ \log_8 3 + \log_8 7 = \log_8 21 \][/tex]
So, the missing value is:
[tex]\[ \boxed{21} \][/tex]
### Part (b)
[tex]\[ \log_4 5 - \log_4 \boxed{\phantom{}} = \log_4 \frac{5}{7} \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b(a) - \log_b(c) = \log_b \left(\frac{a}{c}\right) \][/tex]
we can set up the equation:
[tex]\[ \log_4 5 - \log_4 7 = \log_4 \left(\frac{5}{7}\right) \][/tex]
So, the missing value is:
[tex]\[ \boxed{7} \][/tex]
### Part (c)
[tex]\[ \log_5 \frac{1}{9} = -2 \log_5 \boxed{\phantom{}} \][/tex]
Using the property of logarithms that states:
[tex]\[ \log_b \left(a^c\right) = c \log_b(a) \][/tex]
we rewrite the equation:
[tex]\[ \log_5 \frac{1}{9} = -2 \log_5 3 \][/tex]
Recognize that:
[tex]\[ 3^2 = 9 \][/tex]
and
[tex]\[ \frac{1}{9} = 3^{-2} \][/tex]
Thus,
[tex]\[ \log_5 \frac{1}{9} = \log_5 (3^{-2}) \][/tex]
which simplifies by the logarithmic power rule:
[tex]\[ \log_5 (3^{-2}) = -2 \log_5 3 \][/tex]
So, the missing value is:
[tex]\[ \boxed{3} \][/tex]
To summarize, the missing values are:
(a) [tex]\(\boxed{21}\)[/tex]
(b) [tex]\(\boxed{7}\)[/tex]
(c) [tex]\(\boxed{3}\)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.